Development Of Seo Performance Of Selected Slovak University Web Portals - Miklošík, Andrej (Communication Today, 2025)
This article deals with the issue of performance of faculties at Slovak universities in the ﬁeld of marketing im-plementation in search engines, offering economically oriented studies. We have realized a primary research oriented at determining the situation of the search engine visibilities of the selected 21 faculties. The aim of the article is to determine the overall trends in this area and to ﬁnd the solutions to improve the performance in the respective criteria. We have prepared a set of recommendations for the leader of the rankings, the Faculty of Man-agement, Comenius University in Bratislava, to move forward and strengthen its positions in this market segment.